(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The world is now becoming concrete jungles. Among them Aathi was a nature utopia filled with water and serene people. It had its own culture and Aathi was a lifestyle. Into it comes a modern man, the lost son of Aathi, Kumaran. He is no outsider but now has become one. He uses foreign capital for exploitation and personal greed rather than development. His attempts to control the people as well as the culture can be seen similar to colonizers. The erosion of culture, the resistance that comes from within Aathis are attempts of decolonization. The paper attempts to critique the notions of development and show how globalization becomes the modern colonization.